Improving sustainable practices in tuna purse seine fish aggregating device (FAD) fisheries worldwide through continued collaboration with fishers - Murua, Jefferson; Moreno, Gala; Dagorn, Laurent; Itano, David; Hall, Martin; Murua, Hilario; Restrepo, Victor (Frontiers in Marine Science, 2023)
More than a decade of bottom-up collaborative workshops and research with fishers from the principal tropical tuna purse seine fleets to reduce ecological impacts associated with the use of fish aggregating devices (FADs) has yielded novel improved sustainable fishing practices in all oceans. This integrative effort is founded on participatory knowledge-exchange workshops organized by the International Seafood Sustainability Foundation (ISSF), referred to as “ISSF Skippers Workshops”, where scientists, fishers, and key stakeholders examine and develop together ways and tools to minimize fishery impacts. Workshops organized since 2010 have reached fleet members in 23 countries across Asia, Africa, the Americas, Europe, and Oceania, with over 4,000 attendances, mostly skippers and crew, operating in the Indian, Atlantic, and Pacific oceans. Structured and continued open transparent discussions on ocean-specific options to minimize FAD associated bycatch, ghost fishing and marine pollution have produced an array of novel co-constructed solutions and a better understanding of ecosystem and fishery dynamics. Dedicated at sea research cruises in commercial purse seiners have enabled testing some of the ideas proposed in workshops. Results obtained were then communicated back to fishers for a double loop learning system resulting in solution refinement and/or adoption. Furthermore, fishers’ increased trust and stewardship have stimulated unprecedented large-scale science-industry research projects across oceans, such as multi-fleet biodegradable FAD trials, the adoption and widespread use of non-entangling FADs, and the development and adoption of best practices for the safe handling and release of vulnerable bycatch. This model of collaborative research is broadly applicable to other natural resource conservation fields. Support for long-term inclusive programs enabling harvesters to proactively collaborate in impact mitigation research contributes to improved scientific advice, voluntary compliance, and adaptive management for lasting sustainability trajectories.